2022
DOI: 10.1186/s13018-022-03422-9
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of acetabular cup placement during anterolateral supine total hip arthroplasty using intraoperative fluoroscopy: a retrospective study

Abstract: Background In our institution, total hip arthroplasty (THA) is performed using the anterolateral supine (ALS) approach with intraoperative fluoroscopy. This study aimed to investigate and review the accuracy of acetabular cup placement in ALS-THA using intraoperative fluoroscopy. Methods A total of 142 patients with 154 joints (mean age 64.3 years, 30 males and 112 females) underwent ALS-THA with intraoperative fluoroscopy at the same institution. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Intraoperative uoroscopy is useful not only for con rming cup depth but also for determining cup abduction angle and anteversion. Cho et al reported that the accuracy of cup placement in ALS THA using uoroscopy is good and compares favorably with other navigation systems [14]. The use of uoroscopy in supine surgery not only con rms the position of the cup but also con rms the placement of the stem on the femoral side.…”
Section: Discussionmentioning
confidence: 99%
“…Intraoperative uoroscopy is useful not only for con rming cup depth but also for determining cup abduction angle and anteversion. Cho et al reported that the accuracy of cup placement in ALS THA using uoroscopy is good and compares favorably with other navigation systems [14]. The use of uoroscopy in supine surgery not only con rms the position of the cup but also con rms the placement of the stem on the femoral side.…”
Section: Discussionmentioning
confidence: 99%
“…We performed all THAs using the acetabular component-first technique, and subsequently, the femoral component was placed; however, broaching the femur before preparing the acetabulum, also known as the “combined anteversion technique”, was reported to contribute to reducing dislocation [ 21 , 29 , 30 ]. To the best of our knowledge, we considered that if the acetabular component was placed accurately, the dislocation rate did not markedly increase even when THA was performed using the acetabular component-first technique [ 14 , 15 , 16 , 19 ]. No dislocations occurred during our study period.…”
Section: Discussionmentioning
confidence: 99%
“…Even without a navigation or robotic system, the use of fluoroscopy may improve postoperative outcomes by reproducing GFO and LLD close to those of the pre-operative plan [ 34 , 35 ]. Therefore, we considered that adopting our findings to perform THA in the supine position, such as the anterolateral supine or direct anterior approach, is more reasonable to confirm GFO, LLD, and SGL using intra-operative fluoroscopy [ 16 ]. Despite these limitations, to our knowledge, this is the first report to use the 3D method to measure these parameters and obtain optimal GFO and SGL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation